Room‐/High‐Temperature Mechanical Properties of Titanium Matrix Composites Reinforced with Discontinuous Carbon Fibers. Issue 4 (31st October 2021) - Lv, Shun; Li, Jinshan; Li, Shufeng; Kang, Nan; Chen, Biao
Abstract : The reinforcing effect of short carbon fibers (CFs) in Ti−6Al−4V (TC4) matrix composites fabricated by powder metallurgy is investigated by mechanical testing at room/high temperatures. Different mass fractions of CFs (0−3%) are dispersed into TC4 matrix by high‐energy ball milling. CFs/TC4 powder mixtures are then consolidated by hot isostatic pressing to obtain CFs/TC4 composites. Microscopic morphology, phase composition, and interfacial microstructure of CFs/TC4 composites are thoroughly characterized by various electron microscopies and Raman spectra. It is found that all composites fail before yielding at room‐temperature tensile tests, which is due to the unpleasant bonding condition between CFs and TC4. However, the 1% CFs/TC4 composite fractures in a ductile mode at elevated temperatures. The reinforcing effect of CFs becomes more prominent with the increase in testing temperature. At 700 °C, the 1% CFs/TC4 composite registers 74% improvement in the yield strength compared with the TC4 matrix, which suggests the excellent reinforcing effect of CFs among available reinforcements in the literature. The results suggest that short CFs might be a suitable reinforcement candidate for high‐temperature applications of titanium matrix composites. Abstract : In titanium matrix composites reinforced with discontinuous carbon fibers (CFs), the enhancement of CFs becomes more prominent with increasing tensile temperature. This phenomenon can be attributed to the multiple load transfer forms of CFs, as CFs fractures and pull‐outs are found in the fractographs.